Research on future space-ground integrated information network based on edge-intelligence collaborative - Xu ZHOU; Taixin LI; Yifang QIN; Junping SONG (Dianxin kexue)
With the increase of needs for application,how to provide efficient network services in heterogeneous networking environment and large scale of time and space becomes a new challenge.A future space-ground integrated information network architecture was proposed based on the analysis of future needs,which was called edge-intelligence collaborative-based heterogeneous space-ground integrated identifier network.Three key technologies were introduced:service ID modeling and distribution,resource self-awareness in heterogeneous network,and integration of space-ground heterogeneous network.Finally,the application scenarios in high-speed railway,civil aviation,inclusive services,and military were introduced.